Scenario Based Requirement Engineering (SBRE) in eXtreme Programming (XP) through Agile Modelling (AM) - Kunwar, Sundar (SCITECH Nepal, 2018)
Software development methodologies have been enhancing significantly all the time and have drawn the attention of software professionals from past few years. The software development methodologies are expanding rigorously with wide range of diverse fields and have become more complex demanding the agility to rapidly changing needs of the customers. As a result, agile software development methodologies have evolved and gaining popularity day by day. Agile software development methodologies have come up with modifications demanded in traditional software development process to make them faster; more flexible, light weighted and productive. Extreme Programming (XP) is one of the well-known agile software development methodologies and is driven by a set of values including simplicity, communication, feedback and courage. Planning game, very short release stories and test first coding are some interesting extreme practices of XP; however, it is criticized for some deficiencies like light weight requirement, onsite customer, pair programming and so on. The study has only focused on only one of the most criticized extreme practice-lightweight requirement and has followed agile modelling approach to make improvement on requirement engineering process in XP. Requirements are the user stories that consist of a few sentences (1-3 sentences) written on an index card which describes the functionality given by single onsite customer in XP. There is lack of analysis of stakeholders and their roles in requirement process. Therefore, it is very difficult to know the specific requirements of the specific stakeholder in XP. This means that the requirement engineering process is incomplete in XP. This may result high chances of providing deficient requirements. Agile Modelling (AM) is the chaordic practice based methodology for effective modelling. The interesting part of AM is that it does not tell how to model, but tells about how to be effective as modellers. A Scenario Based Requirement Engineering (SERE) is proposed using AM as alternative to light weighted requirement which one of the most criticized extreme practice of XP. SERE is the implemented description of techniques that helps to understand the task related activities and also facilitates communication among stakeholders and experts. Stakeholders are analysed for understanding a system by identifying the stakeholders in the system and assessing their respective requirements and influence on the system. This will help to get better requirements for system development, but still needs to be validated.